A CASE REPORT of Lichen Nitidus on the Penis: Tiny but Annoying Eruptions - Wang J; Pan Y; Wei G; Mao H; Liu R; Xiong X; Xu J; He Y (Dove Medical Press, 2022)
Jingying Wang, Yinghao Pan, Guangmin Wei, Hanxiao Mao, Rulan Liu, Xia Xiong, Jixiang Xu, Yuanmin He Department of Dermatology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of ChinaCorrespondence: Yuanmin He, Department of Dermatology, The Affiliated Hospital of Southwest Medical University, No. 25 of Taiping Road, Luzhou, Sichuan, 646000, People's Republic of China, Email heym88@163.comAbstract: Most patients are anxious about the skin lesions on the penis. This study reports a case of lichen nitidus on the penis and reviews related literature. A 40-year-old male has presented with small papules with skin color on the penis for one year. The patient was diagnosed with lichen nitidus, and tacrolimus cream and humectant were topically administered after diagnosis. The symptoms were alleviated after treatment. We first report a series of the cases with lichen nitidus on the penis, knowing the clinical and pathological manifestations of this disease can reduce misdiagnosis and unnecessary treatment.Keywords: Lichen nitidus, penis, pathological feature, treatment, prognosis